Building an Expert Critiquing System: ESSENTIAL-ATTENDING - Miller, P. L. (Methods of Information in Medicine, 1986)
This paper describes a “system-building system”, ESSENTIAL-ATTENDING (E-ATTEND-ING), designed to assist in the implementation of expert systems which critique a physician’s plan for patient care. E-ATTENDING has been refined during the implementation of several developmental critiquing systems and may be applied in areas of medical management, patient workup, and differential diagnosis. E-ATTENDING is currently designed to help implement a class of critiquing systems in a subset of possible critiquing domains. It can also be augmented in various ways by interested users to accommodate critiquing domains with more complexity.
Keywords: Artificial Intelligence in Medicine; Computer-assisted Medical Decision-making; Expert Systems; Knowledge Engineering